Tissue-Specific Oxysterols as Predictors of Antidepressant (Escitalopram) Treatment Response in Patients With Major Depressive Disorder - Sun, Zuoli; Yang, Jian; Zhou, Jia; Zhou, Jingjing; Feng, Lei; Feng, Yuan; He, Yi; Liu, Min; Li, Yuhong; Wang, Gang; Li, Rena (Biological psychiatry global open science, 2023)
There is growing evidence that disturbances in cholesterol metabolism may be involved in major depressive disorder (MDD). However, it is not known if cholesterol metabolites present in the brain and periphery can be used to diagnose and predict an MDD patient’s response to antidepressant treatment. A total of 176 subjects (85 patients with MDD and 91 healthy control subjects) were included in this study. The expression of peripheral and brain-specific oxysterols and related gene polymorphisms were investigated in all subjects. The severity of depression was measured using the 17-item Hamilton Depression Rating Scale, 16-item Quick Inventory of Depressive Symptoms–Self-Report, and Patient Health Questionnaire-9 for all patients with MDD before and after 12 weeks of antidepressant treatment. Patients with MDD expressed higher plasma levels of 24(S)-hydroxycholesterol (24OHC) (mainly secreted from the brain) compared with healthy control subjects, and the higher levels of 24OHC were associated with 24OHC synthetase (CYP46A1) gene polymorphisms. In patients with MDD, an improved response to the 12-week antidepressant treatment was associated with a reduction of both 24OHC and 27OHC (mainly secreted from the peripheral system) levels relative to baseline levels. Nonresponders exhibited increased levels of oxysterols at the end of treatment compared with baseline. The superior reduction in oxysterol levels correlated with better outcomes from the antidepressant treatment. These data suggest a potential role for oxysterols as diagnostic and treatment response–related indicators for MDD.